2010
DOI: 10.1021/ie100204x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bimodality on the Adhesive Properties of Pressure Sensitive Adhesives: Role of Bimodal Particle Size and Molecular Weight Distributions

Abstract: A one-pot, two-step miniemulsion polymerization approach was successfully used to create poly(2-ethyl hexyl acrylate/methyl methacrylate/acrylic acid) pressure sensitive adhesives with well-defined and predictable bimodal particle size distributions (PSDs) or bimodal molecular weight distributions (MWDs). The resulting viscoelastic (shear storage and loss moduli) and adhesive properties (i.e., loop tack, peel strength, and shear strength) were tested and compared to monomodal distributions of either particle s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…12, the higher the particle size (41, 122 and 316 nm for 10%, 18% and 25% of BGMAH, respectively) the higher are tack, peel and shear resistance values. Qu et al [48] and Fonseca et al [47] reported the similar findings. However, their copolymers had fixed copolymer composition and similar gel phase, MWD and T g values.…”
Section: Psa Propertiessupporting
confidence: 67%
See 1 more Smart Citation
“…12, the higher the particle size (41, 122 and 316 nm for 10%, 18% and 25% of BGMAH, respectively) the higher are tack, peel and shear resistance values. Qu et al [48] and Fonseca et al [47] reported the similar findings. However, their copolymers had fixed copolymer composition and similar gel phase, MWD and T g values.…”
Section: Psa Propertiessupporting
confidence: 67%
“…PSD mainly influences film formation and latex viscosity; however, it has also been shown to affect adhesive properties [27,47,48]. Despite the fact that all the emulsions had monomodal PSD (Fig.…”
Section: Psa Propertiesmentioning
confidence: 95%
“…[9,10] Qie and Dub e [9] produced butyl acrylate/methyl methacrylate/hydroxyethyl methacrylate/acrylic acid emulsion latexes that showed remarkable improvements to shear strength without compromising tack. Some interesting ideas on overcoming this have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the cohesion of the PSAs without sacrifices in the tack and peeling strength, KH560, a siloxane with unique and better dry and wet adhesion properties, was selected to modify the polyacrylate PSA. In contrast to the decreases in the tack and peeling strength of the PSA modified by the commonly used vinyl silicone, 44 PSA modified by KH560 showed a better adhesive performance. Table V shows that when the content of KH560 was in excess of 2.0 wt % of the total monomer, the tack and peeling strength decreased slightly.…”
Section: Effect Of Siloxane On the Microstructure And Adhesive Propermentioning
confidence: 75%